(untitled) (Shiksha Shastra Saurabh, 2018)
“Sports is an institutionalized comparative activity that involves various physical extensions or the use of relatively complex physical skills by individuals whose participation is motivated by combination of intrinsic and extrinsic factors.” Present situation of sports in Ilam district entitled research was conducted in Ilam, where forty-seven (47) sports related persons were selected as respondents for the study. The main objectives of the study were to find out the developmental trend, present status and prospect of sports in Ilam district. For this study convenient cum purposive sampling method was used. Different sets of interview schedule was developed including overall issues of the developmental trend present status of sports in Ilam district.